2015
DOI: 10.1039/c5ra06488k
|View full text |Cite
|
Sign up to set email alerts
|

Chlorinated polyethylene (CPE)/ethylene methacrylate copolymer (EMA)/sepiolite nanocomposite via a facile one-step covalent modification technique

Abstract: Graphical Abstract for the article "Chlorinated polyethylene (CPE)/ethylene methacrylate copolymer (EMA)/Sepiolite nanocomposite via a facile one-step covalent modification technique" TOC Facile one-step organo-modification of sepiolite improves polymer-filler interfacial adhesion, thereby advances mechanical property and thermal stability of CPE/EMA/sepiolite nanocomposite. ABSTRACT The work reports a facile one step covalent modification technique of sepiolite needles by in-situ polymerization of ε-caprolact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 68 publications
(87 reference statements)
1
11
0
Order By: Relevance
“…The highest value is achieved by CA film, whereas all bionanocomposites have significantly lower contact angles which is a consequence of the sepiolite clay used to disperse the rGO and ZnO-rGO fillers. As observed by other authors, films of alginate loaded with neat sepiolite show a decrease in the water contact angle due to its strong hydrophilic character, explained by the high density of silanol groups (−SiOH) [ 39 , 56 ]. Moreover, as it can be seen in the SEM micrographs ( Figure 1 c), the addition of rGO and ZnO-rGO enhances the film surface roughness, enlarging the surface area and contributing to the increase of surface wettability [ 57 ].…”
Section: Resultsmentioning
confidence: 80%
“…The highest value is achieved by CA film, whereas all bionanocomposites have significantly lower contact angles which is a consequence of the sepiolite clay used to disperse the rGO and ZnO-rGO fillers. As observed by other authors, films of alginate loaded with neat sepiolite show a decrease in the water contact angle due to its strong hydrophilic character, explained by the high density of silanol groups (−SiOH) [ 39 , 56 ]. Moreover, as it can be seen in the SEM micrographs ( Figure 1 c), the addition of rGO and ZnO-rGO enhances the film surface roughness, enlarging the surface area and contributing to the increase of surface wettability [ 57 ].…”
Section: Resultsmentioning
confidence: 80%
“…The peaks at 1853 and 1776 cm −1 are attributed to the C=O stretching vibration, the bands at 1493 and 1453 cm −1 are ascribed to C=C stretching of aromatic benzene ring. Moreover, the wideness of the peak at 1706 cm −1 and 1656 cm −1 is owing to overlapping of the carbonyl (C=O) stretching vibration with the coordinated bonded water [25]. These new bands show that the kinds of SMA are chemically grafted onto the surface of SEP. As can be seen, SMA-1000 copolymer, possessing higher maleic anhydride content and lower molecular weight than SMA-EF40, is also efficiently grafted to SEP surface, as well as grafted to HNT.…”
Section: Structural Analysis Of the Modified Nanoclaysmentioning
confidence: 91%
“…The discontinuity of the silica sheets in sepiolite leads to the characteristic structural tunnels, which possess silanol groups (Si-OH) at their edges. [25] [26]. In the polar polymeric matrix, these silanolgroups not only improve the interactions between SEP and the host polymer, but also enhance the dispersion of SEP without any kind of modification [27] [28] [29] [30].…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of modified sepiolite and unmodified sepiolite in this study revealed no significant difference in the final properties of nanocomposites. 20…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of modified sepiolite and unmodified sepiolite in this study revealed no significant difference in the final properties of nanocomposites. 20 Although there is a lot of studies [21][22][23] concerning the effect of sepiolite as a nanofiller in PE or its copolymers, to the best of author's knowledge, there is no report of using this nanofiller in combination with recycled material. In this study, we considered for the first time the thermal and mechanical behavior of recycled HDPE nanocomposites containing sepiolite as nanofiller.…”
Section: Introductionmentioning
confidence: 99%